Tanggung Jawab Platform Digital dan Perlindungan Hak Korban: Analisis Intermediary Liability di Indonesia - Gusti Tiya Yolanda Nur Fadhila (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
A critical evaluation is needed of Indonesia's legal framework in dealing with Online Gender-Based Violence, particularly revenge porn and cyberbullying. The research focuses on evaluating the effectiveness of Indonesia's Intermediary Liability in forcing global Electronic System Operators to takedown illegal content, and the compatibility of Restorative Justice with technical recovery for victims, namely the Right to Erasure. Through a normative-analytical approach, it was found that current administrative sanctions against global Electronic System Operators, such as fines, fail to create a deterrent effect due to jurisdictional constraints. In addition, they often become pseudo-resolutions because the focus on reconciliation ignores the main technical problem, namely the content that is still circulating, which perpetuates the trauma of victims. It is recommended to adopt a Fast-Track Removal mechanism managed by an independent authority with quasi-judicial powers. Furthermore, the establishment of the Right to Erasure as a mandatory and verifiable requirement in every Online Gender-Based Violence Restorative Justice agreement, reinforced by progressive operational sanctions based on the Personal Data Protection Law, is essential for comprehensive protection of victims.